Synthesis and Solution Region Analysis Method of Linear Guide Mechanism - Qian Weixiang; Liu Shuang; Shi Xiaojuan (Jixie chuandong)
A synthesis and solution regions analysis method for linear guide mechanism when the side link and frame are collinear is proposed. The method is based on the theory of motion geometry， all of straight line linkage with Ball point on the coupler is obtained by the analytical method， the dimension and kinematics properties of mechanism are expressed intuitively. The designer calculates the feasible regions that satisfy these constraints by applying some of the architectural kinematic constraints required for the engineering. The proposed method will discard the segments that do not meet the conditions according to the constraints， and then quickly and accurately find the engineering practical mechanism to solve the problem of difficult mechanism optimization. Finally， the correctness and feasibility of the proposed model is verified by the developed linear guide mechanism synthesis and simulation software platform.